Production and immunogenicity of a deoxyribonucleic acid Alphavirus vaccine expressing classical swine fever virus E2-Erns protein and porcine Circovirus Cap-Rep protein - Du, Fuyu; Cao, Zhi; Ye, Zixuan; He, Jun; Zhang, Weijie; Zhang, Ke; Ning, Pengbo (Frontiers in Microbiology, 2022)
Classical swine fever virus (CSFV) and porcine circovirus type 2 (PCV2) are economically pivotal infectious diseases virus of swine. Alphaviral RNA replicon plasmids have been used as an important vector for constructing nucleic acid vaccine. Here, we aimed to construct a recombinant alphaviral plasmid vaccine pSCA1-E2-Erns-Cap-Rep for the prevention and control of CSFV and PCV2. Our results showed that the recombinant alphaviral plasmid vaccine pSCA1-E2-Erns-Cap-Rep was successfully constructed. The vaccine encoding E2 and Erns of CSFV, Cap and Rep of PCV2 can induce E2, Erns, Cap and Rep protein expression. ELISA analysis showed that mice immunizied pSCA1-E2-Erns-Cap-Rep plasmid vaccine produced higher anti-CSFV and anti-PCV2 specific antibodies with dose- and time-dependent manners. Furthermore, neutralizing assays were measured using IF and ELISA methods. Results showed the production of neutralizing antibody could neutralize CSFV (up to 210.13) and PCV2 (28.6) effectively, which exhibited the immune efficacy of pSCA1-E2-Erns-Cap-Rep plasmid vaccine. Taken together, this pSCA1-E2-Erns-Cp-Rep plasmid vaccine could be considered as a novel candidate vaccine against CSFV and PCV2.